Curious creatures - Cleave, Andrew (Creatures of the ocean., 2020)
Presents an illustrated look at the unique adaptations and behaviors of creatures around the world. Describes how they use these adaptations and behaviors for deception, defense, camouflage, reproduction, and survival. Includes dozens of color photographs, further reading, internet resources, and QR codes that link to educational videos.